Treatment of chronic generalized periodontitis using miramistin-containing nanomatrix as maintenance therapy: a pilot study and early results - Yu. A. Bakaev; Z. S. Khabadze; O. S. Mordanov; Yu. A. Generalova (LLC "Endo Press", 2020)
Aim of the study was to evaluate the clinical efficacy of a nanomatrix with Miramistin based on M-Chip (Double White, Russia), which is used subgingivally as an addition to SRP (scaling and root planing) as a combination therapy in patients with chronic generalized periodontitis.Materials and methods. T he s tudy i ncluded 4 5 p atients w ith c hronic g eneralized p eriodontitis (20 f emales a nd 25 males; age span is 35-60 years; mean age 57.87 ± 8.2 years). Patients with a probing depth ≥5 mm were included. Selected patients did not receive antibiotic therapy during the last 6 months of follow-up.Results. The mean clinical parameter values between the M-Chip + SRP treatment group and the SRP control group showed a statistically significant improvement in clinical parameters at 6 months compared to baseline values for the following indicators: plaque index (API), gingival pocket depth at probing, Mühlemann Bleeding Index (BI), the level of clinical attachment.Conclusions. SRP has been shown to be effective in reducing pocket depth, increasing periodontal attachment, and reducing inflammation. However, when SRP was used with the M-Chip, possible additional clinical benefits have been shown.